The Use of Personal Deixis in The Netflix Series “Losmen Bu Broto The Series” in 2025 - Herawati, Yuke Elvin; Sucipto; Padmasari, Arumtyas Puspitaning (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
In this study using a serial film that can be focused on conversations containing deixis phenomena in the Netflix serial film "Losmen Bu Broto The Series" in 2025. The purpose of this study is to describe the use of personal deixis in the Netflix serial film "Losmen Bu Broto The Series" in 2025, This research approach uses a qualitative approach. The data and data sources used in this study are deixis words and sentences in the conversation of the Netflix serial film "Losmen Bu Broto The Series". The appropriate data collection method is the documentation method and the data collection technique is the listening technique and note-taking technique. In the validity of the data in the study, it was carried out by the method of increasing perseverance. Data analysis carried out in this study used a descriptive method, namely describing the findings in the study with content analysis techniques. The results of this study are several types of deixis in pragmatics, including first person pronouns singular, first person pronouns plural, second person pronouns singular, second person pronouns plural, third person pronouns singular, third person pronouns plural in the serial film